PERENCANAAN PENURUNAN BIAYA PRODUKSI ASAM AMINO MENGGUNAKAN ANALISIS SWOT DAN TOWS DI PT. ABC - Sumantri, Bambang; Hidayatullah, Samudra Syarif Wahyu; Wiryanto, Ibnu; Fauzi, Moh. Hilal; Hariastuti, Ni Luh Putu (Universitas Nusantara PGRI Kediri, 2024)
Amino acids are chemicals needed by living beings to develop because they are the main components of protein compounds. PT. ABC, one of the largest amino acid producers in Indonesia and the longest-established in Southeast Asia, is a factory with extensive experience in amino acid production. PT. ABC, a chemical manufacturing company whose products are used in various industries, requires an appropriate strategy amid tight business competition. The aim of this study is to provide recommendations for strategies to reduce production costs to enhance PT. ABC's competitiveness. The research method uses a descriptive SWOT analysis method with IFAS and EFAS matrices. In the 9-quadrant SWOT analysis, PT. ABC is positioned in Quadrant I (concentration through vertical integration) with a score of 3.19 (IFAS) and 3.14 (EFAS), indicating that the company is in very healthy condition. Meanwhile, in the 4-quadrant diagram, PT. ABC is positioned in Quadrant I, meaning the situation is advantageous for the company, possessing opportunities and strengths to exploit these opportunities. Then, a TOWS matrix was created based on the conducted SWOT analysis. In the TOWS analysis, mapping of Strength-Opportunity, Strength-Threats, Weakness-Opportunity, Weakness-Threats was conducted. Strategies were then formulated to reduce production costs by leveraging opportunities into strengths, turning threats into company strengths, transforming weaknesses into company opportunities, and managing threats and weaknesses to find solutions for reducing production costs.